Jerry Waldie Governor Campaign Fresno Headquarters - Watkins, Howard K. (1974)
Waldie speaking, campaign logo, Ruth Wall, ?, ?, ? , Jerry Roberts , ?, ?, ? Tom Kipps outside window, inside Anne Kipps w/Waldie hat and holding cake she made